Preliminary Evidence of Children's Weight Gain From 5 Months of Home Quarantine During the COVID-19 Pandemic. Issue 2 (March 2022) - Brazendale, Keith; Garcia, Jeanette; Hunt, Ethan T.; Blankenship, Michael; Eisenstein, Daniel; Leon, Ana
Purpose . Preventive measures to curtail the spread of the Coronavirus Disease 2019 (COVID-19)—such as home quarantine, closure of schools/programs—are necessary, yet the impact of these restrictions on children's weight status is unknown. The purpose of this case report was to investigate changes in children's body mass index (BMI) and zBMI during COVID-19 quarantine. Methods . Children had their heights and weights recorded early March 2020 (pre-COVID-19) and 5 months later (early August 2020). Paired sample t tests examined changes in BMI and zBMI from baseline to follow-up. Results . Twenty-nine children (62% female; mean age 9.3 years; 27.5% with overweight or obesity) provided height and weight data at both time points. There was a significant difference in pre-COVID-19 BMI (mean [M] = 20.1, standard deviation [SD] = 6.0) and follow-up BMI (M = 20.7, SD = 6.4); t (57) = −3.8, P < .001, and pre-COVID-19 zBMI (M = 0.8, SD = 0.9) and follow-up zBMI (M = 0.9, SD = 0.9); t (57) = -3.1, P = .003. Five of the 29 children moved from normal weight to overweight (n = 4) or obese (n = 1) during 5 months of quarantine. Conclusions . Preliminary evidence shows most children increased their BMI and zBMI values from pre-COVID-19 assessment to the follow-up assessment, 5 months later. These initial findings identify potential incidental negative health consequences of children as a result of COVID-19 preventative measures such as home quarantine.